Desalination of seawater using several types of cyanobacteria - Eman Said Hosni Dahmash; Nabil M. Abdelmonem (2022)
(3jgOa gPG GdHMK Edi OQGSI bOQI GdWMGdH Ydi JMdjI ejGg GdHMQ dJMOjO CaVd SdGdGJ GdWMGdH h JQcjRgG h Ref GdESJHbGA GdCfSH ddMUhd Ydi CaVd caGAI dJNajV edhMI ejGg GdHMQ(B. (3CXgQJ GdfJGFL GdeYedjI Cf SdGdI (BAnabaena oryza (3h SdGdI (BNostoc muscorum (3gj CcKQ GdSdGdGJ EeJUGUkG ddedhMI NdGd (B30(3ObjbI HfSHI (B24.87 %. (3Enqf GSJNOGe GdWMGdH gh CSdhH hGYO dJMdjI ejGg GdHMQ h jbJQM Cf jJe OeLg eY WQjbI UfGYjI CNQi cGdJfGVM GdYcSj ddMUhd Ydi CaVd GdfJGFL HCbd JcdaI hESJgdGc ddWGbI(B.s
Thesis (M.Sc.)-Cairo University,Faculty of Engineering,Department of Chemical Engineering.
Bibliography: p. 103-107.
Keywords: Chemical Engineering; Thermal distillation